2016
DOI: 10.1111/scs.12361
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of working carers of older people regarding access to a web‐based family care support network offered by a municipality

Abstract: Policy makers in Sweden and other European Member States pay increasing attention as to how best support working carers; carers juggling providing unpaid family care for older family members while performing paid work. Exploring perceived benefits and challenges with web-based information and communication technologies as a means of supporting working carers' in their caregiving role, this paper draws on findings from a qualitative study. The study aimed to describe working carers' experiences of having access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…the one-third of carers who indicated that they were unable to access support groups during the day due to work, the 40% who had no time to use carer support due to their work and care commitments, and the 25% that indicated a preference for anonymity when meeting other carers. ICTmediated forms of support would clearly have application for such carers, as also described by Andersson et al [21]. A preference for physical meetings with other carers rather than ICT-mediated meetings may be related to experiencing fewer digital skills or the view that communication is too impersonal when not involving synchronous interaction or physical contact [21].…”
Section: Perceived Value Of Ict-mediated and Non-ict Forms Of Supportmentioning
confidence: 95%
See 1 more Smart Citation
“…the one-third of carers who indicated that they were unable to access support groups during the day due to work, the 40% who had no time to use carer support due to their work and care commitments, and the 25% that indicated a preference for anonymity when meeting other carers. ICTmediated forms of support would clearly have application for such carers, as also described by Andersson et al [21]. A preference for physical meetings with other carers rather than ICT-mediated meetings may be related to experiencing fewer digital skills or the view that communication is too impersonal when not involving synchronous interaction or physical contact [21].…”
Section: Perceived Value Of Ict-mediated and Non-ict Forms Of Supportmentioning
confidence: 95%
“…These are increasingly recognized as innovative means to increase accessibility of, and flexibility in, support [20]. ICT-mediated support, such as support available via the Internet, has been proposed as a means to provide Swedish working carers with flexible access to information, psychosocial support, and learning opportunities, which would otherwise be difficult to obtain due to limited time while working and providing care [21,22]. Such forms of ICT-mediated support and social, peer-topeer, and emotional support have been reported to reduce carer burden [23,24] and stress [25][26][27].…”
Section: Support For Working Carersmentioning
confidence: 99%
“…The computerization of patient health records and online access to readily available data enables the working ICGs to access information, receive psychosocial support from the professional counterpart and benefit from potential learning opportunities [45], but also brings into play the question of transparency. The main concerns of the formal CGs center on security and patient privacy and the ethics of processing and transmitting sensitive data outside the professional sphere; not only can this undermine the completeness, and hence usefulness, of the data transmitted to the ICG, but also can make the formal caregivers reluctant to share electronic data files with them [46].…”
Section: Transparency Of Information Flow Between Formal and Informalmentioning
confidence: 99%
“…Transparency of information flow is often impeded by fears over security and loss of privacy. A foundational concept of information sharing in healthcare is to avail patient health and biography information only to the authorized providers of care as concerns of confidentiality may be seen to outweigh benefits of quality of care [45]. Patient engagement and family caregiver access to portals may improve self-regulated disease management.…”
Section: Transparency Of Information Flow Between Formal and Informalmentioning
confidence: 99%
See 1 more Smart Citation